Artificial Intelligence and the Skill Premium - David E. Bloom; Klaus Prettner; Jamel Saadaoui; Mario Veruete (Institute of Labor Economics (IZA), 2024)
How will the emergence of ChatGPT and other forms of artificial intelligence (AI) affect the skill premium? To address this question, we propose a nested constant elasticity of substitution production function that distinguishes among three types of capital: traditional physical capital (machines, assembly lines), industrial robots, and AI. Following the literature, we assume that industrial robots predominantly substitute for low-skill workers, whereas AI mainly helps to perform the tasks of high-skill workers. We show that AI reduces the skill premium as long as it is more substitutable for high-skill workers than low-skill workers are for high-skill workers.
Keywords: J30; O14; O15; O33; 330; automation; artificial intelligence; ChatGPT; skill premium; wages; productivity